2021
DOI: 10.4274/ejbh.2020.5961
|View full text |Cite
|
Sign up to set email alerts
|

Phyllodes Tumors of the Breast: A Single-Center Experience

Abstract: Phyllodes tumors (PTs) of the breast are rare fibroepithelial tumors that constitute 0.3%-0.5% and 2%-3% of primary breast tumors and fibroepithelial tumors, respectively (1). They may be observed in all ages; nevertheless, they are mostly observed in the age range of 35-55 years (2). They are radiologically and clinically similar to fibroadenomas (FAs); however, they are differentiated from FAs with increased cellularity and metastatic invasion capacity of the local recurrence and malignant types. Although it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 28 publications
1
11
0
1
Order By: Relevance
“…Cytological atypia was not observed, and the mean mitotic figure number per 10 HPF was 1.8 (1-3). On the histological examination of borderline PT, increased stromal cellularity was noted (Figure -4), and the mean mitotic figure number per 10 HPF was 6.6 (5)(6)(7)(8). Nuclear pleomorphism, prominent nucleoli, cytological atypia, bleeding, and necrosis were observed in malignant PT.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Cytological atypia was not observed, and the mean mitotic figure number per 10 HPF was 1.8 (1-3). On the histological examination of borderline PT, increased stromal cellularity was noted (Figure -4), and the mean mitotic figure number per 10 HPF was 6.6 (5)(6)(7)(8). Nuclear pleomorphism, prominent nucleoli, cytological atypia, bleeding, and necrosis were observed in malignant PT.…”
Section: Resultsmentioning
confidence: 99%
“…There is no pathognomonic radiological finding that differentiates between FAs and benign, borderline, and malignant phyllodes tumors. Recent studies have reported that contrast-enhanced MRI findings such as a tumor size over 3 cm, poorly circumscribed and microlobular structure, heterogeneous appearance in echogenicity, hypervascularity, and the presence of internal cystic cavities support PT in the differential diagnosis of two tumors 6,10,12,13 . Moreover, solid components with greater concentration in hemorhagic cystic spaces on MRI suggest PT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations